If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3y = 2400 Solving x + 3y = 2400 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. x + 3y + -3y = 2400 + -3y Combine like terms: 3y + -3y = 0 x + 0 = 2400 + -3y x = 2400 + -3y Simplifying x = 2400 + -3y
| 2n+5=6n-3 | | 5r-3=3r+7 | | 3s+1=2s+5 | | x-4/36 | | (14+8y)=(3y+29) | | X+25=-10 | | f(x)=8x^2-x^3 | | (n-3)(n-3)=0 | | 10+9=119 | | ab+2c+5ba+3c= | | x^3=44 | | 7/x=9-2x | | 2ydx+(x-seny)dy=0 | | -312=-12(8+n) | | 2x^3-19x^2-363=0 | | -75=4b+5 | | 8(-7+x)=-56 | | 207=-2-11v | | 2(11+k)=30 | | 9=3(-8+x) | | -1+2p=41 | | 16+6a=4(a+2)+a | | (1/2)x=64 | | -4+11x=-7(-4x-11)+10x | | 8m-4m=17+9m+3-7m | | x+3+6=-23+5x | | 3(-6-3n)+5n=-2(-8n-1) | | -6x-7x=3x-4x | | (3x-9z)2= | | -6x-7x=3x-4c | | -4+3b+b=-3+3b | | -t^2+16t+40=0 |